Continuous-discontinuous formulation for ductile fracture - Mariana Rita Ramos Seabra (2011)
In this contribution, a continuum-discontinuum model for ductile failure is presented. The degradation of material properties through deformation is described by a Continuum Damage Mechanics model, which uses a non-local integral formulation to avoid mesh dependence. In the final stage of failure, the damaged zone is replaced by a macro crack for a more realistic representation of the phenomenon. The inclusion of the discontinuity surfaces is performed by the XFEM and Level Set Method to avoid the spurious damage growth typical of this class of models.